Uji Kualitas Air Tanah di Distrik Merauke Ditinjau Dari Parameter Total Dissolved Solid (TDS), dan Salinitas - Malesi, Wa Ode Arsyanti Wida; Putra, Don Jaya (Jurnal Sumberdaya Akuatik Indopasifik, 2024)
Merauke District has a characteristic landscape in the form of swampy lowlands formed by sedimentation with low-quality brackish groundwater sources. This study aims to determine the water quality based on the parameters of total dissolved solid (TDS) and salinity in Merauke District. Groundwater samples came from 11 villages with sampling techniques using cluster random sampling techniques. The test results in the laboratory showed that water samples from Rimba Jaya village had the highest TDS value with levels of 5040 mg/l and water samples from Mandala village had the lowest TDS value with levels of 478 mg/l. In the salinity parameter of Rimba Jaya village also has the highest salinity value with 5.34 ppt while the lowest salinity value is found in Mandala village with 0.41 ppt. From the test results on the parameters of TDS and salinity can be concluded that the quality of groundwater in the Merauke District of Papua province is low and does not meet the requirements to be used as a source of drinking water based on the regulation of the Minister of health of the Republic of Indonesia number 492/Menkes/Per/IV/2010.